2012
DOI: 10.3892/mmr.2012.1090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant adeno-associated BMP-4/7 fusion gene on the biology of BMSCs

Abstract: The aim of the study was to investigate the effect of recombinant adeno-associated virus (AAV) with morphogenetic protein 4/7 fusion gene on the ossification of rabbit bone marrow stromal cells (BMSCs). The genes BMP-4 and BMP-7 were obtained through one-step reverse transcriptase polymerase chain reaction from human placental cells. The BMP-4/7 fusion gene was generated through recombination. The rabbit BMSCs were transfected with the recombinant AAV vectors carrying AAV-BMP-4/7 with various multiplicity of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Hakki et al observed that BMP-7 stimulates both ALP activity and biomineralization in a dose-dependent manner to promote the osteogenic differentiation of human periodontal ligament stem cells 26) . The strong odontogenic effects that we observed in our study are consistent with previous reports that used adeno-associated viral vectors in a variety of cell types 27,28) . Additionally, DSPP and OCN have been used as indicators of odontoblastic differentiation.…”
Section: Discussionsupporting
confidence: 82%
“…Hakki et al observed that BMP-7 stimulates both ALP activity and biomineralization in a dose-dependent manner to promote the osteogenic differentiation of human periodontal ligament stem cells 26) . The strong odontogenic effects that we observed in our study are consistent with previous reports that used adeno-associated viral vectors in a variety of cell types 27,28) . Additionally, DSPP and OCN have been used as indicators of odontoblastic differentiation.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, in the present study, we used lentiviral vectors for transfection. Regarding the other transfection vectors, one study used the Adeno-associated virus (AAV) virus vector system to construct the AAV-BMP-4/7 vector, making the screening of recombinant vectors more straightforward, and they successfully built the recombinant AAV-BMP-4/7 virus that carried the BMP-4/7 fusion gene in a relatively short time [30]. This may provide a new tool for BMPs-related gene research.…”
Section: Discussionmentioning
confidence: 99%
“…overexpress genes, such as BMP-4, -7 [125] and BMP-6, claimed to be even more potent proosteogenic factors than BMP-2 in the BMP-2-engineered BM-MSCs [126].…”
Section: Bone Formation Attempts Using Mscsmentioning
confidence: 99%
“…GDF-5 [102][103][104] TIMP-1 [106] Bcl-2 [101] BONE FORMATION BMP-2 [86][109-111] BMP-2/SDF-1β [113] BMP-2/HIF-1α [114] BMP-2/Ang-1 [47] BMP-2/VEGF [116][117][118] BMP-2/miR-148b [142] BMP-4/-6/-7 [125,126] VEGF [119,120] Epo [121] IGF-I [128,129] OGP [127] Leptin [130] PDGF [131] ephrinB2 [132] ITGA2 [133] NELL1 [134] β-catenin [135] HI Cb TA Fo Na LIVER REGENERATION VEGF [144] ATP7B [155] HN HN…”
Section: Cartilage Productionmentioning
confidence: 99%